A General Equilibrium Model with Informal Financial Markets. (IMF Working Papers; Working Paper ;, 1991)
The paper presents a general equilibrium framework for short-run macroeconomic analysis in a developing country context where controls on interest rates and foreign exchange restrictions lead to the emergence of informal financial markets. The complexity of the model precludes an analytical treatment. A simulation approach, based on parameters derived from estimates in the existing literature, is used to assess the properties of the model, which differ in important ways from those of standard open-economy models.